THE MODEL OF PROFESSIONAL EDUCATION FOR THE DEVELOPMENT OF STUDENTS’ READINESS FOR INDEPENDENT LEARNING ACTIVITIES IN THE DIGITAL TRAINING ENVIRONMENT (Conferencea, 2024)
This article is to develop students’ readiness for independent educational activities in the environment of digital professional education.